Modeling of professional activities of future teachers in master training conditions - Sabatovska, Inna; Bobokalo, Sergey (ScienceRise: Pedagogical Education, 2019)
The article describes the state of the problem under study on scientific and pedagogical literature and normative documents, specifies the essence of the key concepts of the research, specifies the peculiarities of preparation of future teachers for the professional activity in the conditions of the master's degree. The peculiarities of preparation of future teachers for the professional activity in the conditions of the magistracy through its modeling are substantiated. It is noted, that simulation of the process of professional training for the activities of future teachers provides the basis for answering the question: how to build a learning process, in order to increase the qualities of the personality of the teacher of higher education, sufficient for professional activities. Principal significance is the question of the essence of the profession of a teacher of higher education, the content and competence of his/her duties, the culture of his/her pedagogical influence, his/her values and ideals, and professionalism. It is determined, that preparation of future teachers for the professional activity in the conditions of the magistracy is a process of organization of educational, scientific and pedagogical activity of a master student during his/her studies in the magistracy, aimed at forming his/her readiness for the activity of a teacher of higher education. The purpose of preparing future teachers for the professional activity in the conditions of the magistracy is to form the personality of the future specialist, to ensure his/her professional development and pedagogical skills, professional competence, professionally significant qualities, as well as the ability to carry out a scientific research. The model of preparation of future teachers for the professional activity in the conditions of the master's degree based on the implementation of organizational and methodical conditions is presented